A Solution To Plastic Problems; A Stronger Campaign Or An Innovative Waste Management (Jurnal Kajian Media, 2019)
Plastic pollution has become a huge environmental problem, prompting some cities and countries to heavily tax or ban the plastics products (e.g bags, straws). The purpose of this research is to provide knowledge into the effectiveness of campaigns using plastic and plastic waste, and provide an overview of a new innovative waste management. In this paper, researcher are intended to introduce Masaro (Manajemen Sampah Zero), a CSR program at PT Polytama, as it would be an innovative and efficient waste management instead a massive campaign.Keywords: Plastic problems, Campaign, Waste management